PENGELOLAAN KEUANGAN BISNIS FASHION SHELLA BOUTIQUE - Jayanti, Fitri Dwi; Indarto, Bambang Ahmad; Tantra, Arda Raditya; Ani, Dewi Ari; Nurani, Bulan Karima (Jurnal Bakti Humaniora, 2024)
Since 2019, Shella has been running a boutique business in Puri Anjasmoro Semarang. The business has gradually continued to grow and has an increasing business volume. Good financial management is one of the key factors in business sustainability, including in the fashion boutique business which has the characteristics of a creative business with complex financial management needs. However, many boutique business actors in the MSME sector have not implemented systematic financial records, so they face challenges in monitoring cash flow, evaluating business performance, and accessing funding sources. The methods used include an initial survey to identify the condition of boutique financial management, training in financial records based on a simple system (manual and digital), and direct practical assistance for three months. The main focus of the program is to separate personal and business finances, record income and expenses in a structured manner, and prepare simple financial reports, such as profit and loss and cash flow statements. The results of this activity show a significant increase in the understanding and ability of boutique owners to prepare financial reports. Before the assistance, business actors did not separate personal and business finances, making it difficult to know the profitability of their business. After the activity, boutique owners were able to identify the financial condition of the business more transparently and measurably. In conclusion, education and assistance in recording financial reports have a positive impact on boutique financial management, increasing operational efficiency, and reducing the risk of recording errors. With better financial management, boutiques have the potential to grow more competitively and sustainably in the local and national fashion markets.   Abstrak Sejak 2019 Shella menekuni usaha butik yang ada di puri anjasmoro semarang. Usaha tersebut lambat laun terus berkembang dan memiliki volume usaha yang terus meningkat. Pengelolaan keuangan yang baik merupakan salah satu faktor kunci dalam keberlanjutan usaha, termasuk dalam bisnis fashion butik yang memiliki karakteristik usaha kreatif dengan kebutuhan pengelolaan keuangan yang kompleks. Namun, banyak pelaku usaha butik di sektor UMKM belum menerapkan pencatatan keuangan secara sistematis, sehingga menghadapi tantangan dalam memantau arus kas, mengevaluasi kinerja usaha, dan mengakses sumber pendanaan. Metode yang digunakan meliputi survei awal untuk mengidentifikasi kondisi pengelolaan keuangan butik, pelatihan pencatatan keuangan berbasis sistem sederhana (manual dan digital), serta pendampingan praktik langsung selama tiga bulan. Fokus utama program adalah memisahkan keuangan pribadi dan bisnis, mencatat pemasukan dan pengeluaran secara terstruktur, serta menyusun laporan keuangan sederhana, seperti laporan laba rugi dan arus kas. Hasil dari kegiatan ini menunjukkan peningkatan signifikan dalam pemahaman dan kemampuan pemilik butik dalam menyusun laporan keuangan. Sebelum pendampingan, pelaku usaha tidak memisahkan keuangan pribadi dan usaha, sehingga sulit mengetahui profitabilitas bisnisnya. Setelah kegiatan, pemilik butik mampu mengidentifikasi kondisi keuangan usaha secara lebih transparan dan terukur. Kesimpulannya, edukasi dan pendampingan pencatatan laporan keuangan memberikan dampak positif bagi pengelolaan keuangan butik, meningkatkan efisiensi operasional, dan mengurangi risiko kesalahan pencatatan. Dengan pengelolaan keuangan yang lebih baik, butik memiliki potensi untuk berkembang lebih kompetitif dan berkelanjutan di pasar fashion lokal maupun nasional.